Design and In Vitro Evaluation of Curcumin Dental Films for the Treatment of Periodontitis - Samal, Himansu Bhusan (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The objective of this research was to design and evaluate dental film containing curcumin for the topical treatment of periodontal diseases. Materials and Methods: Curcumin, hydrophobic polyphenolic compounds derived from the rhizomes of Curcuma longa, shows wide spectrum of antibacterial, anti-inflammatory, and antioxidant properties activity against a number of periodontal pathogens and hence selected for site-specific delivery in the treatment of periodontitis. Dental films were prepared by solvent-casting technique using polymers such as ethyl cellulose, hydroxypropyl methylcellulose K4M, and Eudragit RL 100 with polyethylene glycol 400 as plasticizer, and prepared films (F1-F7) were evaluated for various physicochemical parameters such as weight variation, surface pH, folding endurance, moisture loss, moisture absorption, drug content, in vitro drug release, in vitro antibacterial, and stability studies. No chemical interaction between drug and the polymer was seen as confirmed by Fourier transforms infrared spectroscopy studies. Results and Discussions: In vitro dissolution studies showed an initial burst release to achieve immediate therapeutic level of drug in periodontal pocket, followed by a progressive fall and extended release of the drug with more uniformity for prolonged period of time. Formulation F7 released 98.25% of drug at the end of 168 h was considered as the optimized formulation. Release kinetics of curcumin from film followed the Higuchi diffusion model. Stability studies did not show any significant changes with respect to content and appearance. Conclusion: Good physicochemical properties were shown by the films. The study suggests that curcumin dental film is a potential drug delivery device for the topical treatment of periodontal diseases.